Aboriginal and Torres Strait Islanders’ tourism policy : the current state of play / M Whitford - Whitford, M (Faculty of Hotel and management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2009)
Tourism is viewed as a vehicle which can produce an array of benefits for Aboriginal and Torres Strait Islander [ATSI] peoples. Although ATSI tourism is a small sector of the Australian tourism industry, its ability to facilitate diverse benefits should not be underestimated. While numerous Australian Governments have produced tourism policies to facilitate the development of ATSI tourism, the effectiveness and appropriateness of these policies have been questioned. Consequently, the purpose of this study was to determine the degree to which Australian State/Territory Government ATSI tourism policies can facilitate the development of ATSI tourism. This paper describes a qualitative study examining the foci of current Australian State/Territory Governments’ ATSI tourism policies. The study concluded that ideally, these policies should demonstrate a more balanced distribution of foci across the economic, socio-cultural, ecological and political environments to avoid accusations of rhetoric and thus demonstrate a propensity for facilitating long term sustainable outcomes for ATSI tourism.